Os três momentos pedagógicos no ensino de associações de resistores - Barreto, Eloy Oliveira (2018)
We propose, in this work, a didactic sequence which aims to insert the practices that stimulate students' desire to obtain new knowledge and practical and theoretical experiences related to the contents of electrical circuits. This content was chosen because it's something that is part of the daily life of the students and is often not perceived, or not recognized, as being a "school class". The main focus of the sequence presented in this work is to allow the student to develop knowledge about one of the main coadjuvants of their society, the electric circuits and, for students who already have previous knowledge about the content, to improve them so that they can appreciate the electrical equipment in the safest and most efficient way possible, aiming also the integration of the school experience with the daily life of the student, bringing the community closer to school life, since our students will be multipliers and social instigators about the practices related to safety in residential electrical installations . We will put into practice the “Education 4.0”, the “Learning by doing”. Each student will have the opportunity to express themselves, to solve the problems and situations presented according to his previous knowledge. All activities will be carried out according to the pace of each student, so that we can have a general understanding about the subject addressed. Although the work focuses on the study of electrical circuits, there will be total freedom for the exploration of additional contents by students, external or not to electrodynamics.